Chapter 7 Organizational Stress in Contemporary Japan - Ohira, Tsuyoshi (Taylor & Francis, 2021)
Stress is defined as a feeling experienced when a person perceives that demands exceed the personal and social resources the individual is able to mobilize. It can occur due to environmental issues, such as a looming work deadline, or psychological, for example, persistent worry about familial problems. While the acute response to life-threatening circumstances can be life-saving, research reveals that the body's stress response is largely similar when it reacts to less threatening but chronically present stressors such as work overload, deadline pressures and family conflicts. It is proffered that chronic activation of stress response in the body can lead to several pathological changes such as elevated blood pressure, clogging of blood vessels, anxiety, depression, and addiction. Organizational Stress Around the World: Research and Practice aims to present a sound theoretical and empirical basis for understanding the evolving and changing nature of stress in contemporary organizations. It presents research that expands theory and practice by addressing real-world issues, across cultures and by providing multiple perspectives on organizational stress and research relevant to different occupational settings and cultures. Personal, occupational, organizational, and societal issues relevant to stress identification along with management techniques/approach to confront stress and its associated problems at individual and organizational level are also explored. It will be of value to researchers, academics, practitioners, and students interested in stress management research.